Assessment on physical factors of thermal comfort, sick building syndrome symptoms and perception of comfort among occupants in a public research university laboratory building - Rohizan, Nurul Atikah; Zainal Abidin, Emilia (Community Health Society Malaysia, 2015)
Background: Sick Building Syndrome (SBS) is a phenomenon where people have a range of symptoms related to a certain building conditions, most often a workplace. Physical environmental factors is one of the contributors of SBS. This study aimed to determine the association between SBS symptoms and perception of comfort with physical factors among occupants in offices at a public university in Malaysia.